2012
DOI: 10.3109/13693786.2011.587211
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology ofCandidablood stream infections in patients with hematological malignancies or solid tumors

Abstract: Invasive Candida infections are associated with high morbidity and mortality. Due to an increased incidence in patients with hematological or oncological malignancies, fluconazole prophylaxis became a common practice in many centers in the late 1990s. Until recently, there was insufficient data on the effect of the use of azoles on the incidence of Candida blood stream infections and species distribution. Here we present a single center retrospective study of the epidemiology of Candida blood stream infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 26 publications
6
44
1
3
Order By: Relevance
“…Patients with proven IFI was reported to need antifungal therapy switching compared to patients with probable or possible IFI (33 vs. 25 and 7 %, respectively) [27]. Candida albicans (nine cases) predominated among fungal pathogens responsible for blood stream infections in our study as reported in other studies [28]. Two patients who died of Candida parapsilosis related blood stream infection yielded this species in sputum and wound cultures that revealed colonization.…”
Section: Discussionsupporting
confidence: 66%
“…Patients with proven IFI was reported to need antifungal therapy switching compared to patients with probable or possible IFI (33 vs. 25 and 7 %, respectively) [27]. Candida albicans (nine cases) predominated among fungal pathogens responsible for blood stream infections in our study as reported in other studies [28]. Two patients who died of Candida parapsilosis related blood stream infection yielded this species in sputum and wound cultures that revealed colonization.…”
Section: Discussionsupporting
confidence: 66%
“…Surprisingly, the current study found that most cases of candidemia were caused by C. parapsilosis (34.4%) and C. glabrata (28.1%). Historically, C. albicans and C. glabrata were reported to be the most frequently identified yeasts isolated from blood cultures worldwide; however, in the recent years, the proportion of infections caused by species other than C. albicans has markedly increased and C. parapsilosis is now one of the leading causes of invasive candidal disease (5,14,15). The current study's findings are in agreement with those of Das et al who recently reported that 58% of episodes of candidemia were caused by non-albicans Candida (16).…”
Section: Discussionmentioning
confidence: 99%
“…are the most prevalent fungal pathogens, and C. albicans is the most commonly isolated species from patients with candidemia. Nevertheless, other Candida species have emerged as clinically important opportunistic pathogens (3)(4)(5)(6). Resistance to antifungal agents is becoming increasingly prevalent in Candida species (7).…”
Section: Introductionmentioning
confidence: 99%
“…Candida albicans is known as a biofilm former. Bloodstream infections are frequently associated with the use of a catheter, and the catheter can be a scaffold for biofilms (2). Once biofilms are formed, the biofilms continuously supply detaching cells as a source of infection; thus, biofilm-related infection is associated with a poor prognosis (2,3).…”
mentioning
confidence: 99%
“…Bloodstream infections are frequently associated with the use of a catheter, and the catheter can be a scaffold for biofilms (2). Once biofilms are formed, the biofilms continuously supply detaching cells as a source of infection; thus, biofilm-related infection is associated with a poor prognosis (2,3). Recently, research into molecular mechanisms related to biofilm formation has revealed transcriptional regulation (4); however, the majority of these related studies lack realtime observation of the development process, and therefore, the fate of the biofilm and the effects of antifungals against biofilms are not clearly understood.…”
mentioning
confidence: 99%